Creation of unpublished texts, an assertive strategy in the classroom - Gómez Rojas, Yaneth; Gómez Rojas, Yaneth; Torres Alarcón, Patricia; Varón Bedoya, Merly Astrid (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The purpose of this research was to analyse, within the school context, flaws and weaknesses presented by fifth grade students of the Educational Institution“Álvaro González Santana”, “Rosario” and “Manitas” branches whose objective was to encourage students on the creation of unpublished texts that express the reality of their context. This proposal included a qualitative methodology of socio-critical type, with a research action, where the findings show that the students, in their majority, present neglect at the moment of the textual creation, evidenced in the low level of written production, lack of cohesion, coherence, construction of sentences and structuring of ideas. It was possible to demonstrate that, when taking innovative strategies to the students, their creation of written texts was enriching, the so-called neglect went into the background and an interesting moment of creation was activated.